The deadly facets of terrorism. Issue 4 (24th July 2019) - Python, Andre; Illian, Janine B.; Jones‐Todd, Charlotte M.; Blangiardo, Marta
Abstract : Can Bayesian models reveal the underlying processes that drive the lethality of non‐state terrorism at a local level? Andre Python, Janine B. Illian, Charlotte M. Jones‐Todd and Marta Blangiardo investigate Abstract : Can Bayesian models reveal the underlying processes that drive the lethality of non‐state terrorism at a local level? Andre Python, Janine B. Illian, Charlotte M. Jones‐Todd and Marta Blangiardo investigate.